Implementasi Multipath Routing menggunakan Algoritme Iterative Deepening Depth First Search pada OpenFlow Software-Defined Networking - Ignatius Suryo Wicaksono; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
One of the main problems of the implementation of multipath routing is how to find the paths. In this research, Iterative Deepening Depth First Search (IDDFS) algorithm was used. The performance of IDDFS algorithm was measured by comparing IDDFS with other algorithms: Breadth First-Search (BFS) and Depth First-Search (DFS). Some parameters used to measure the performance of algorithms were path search, multipath, path execution time, response time, and throughput. The measurement was done by using simple topology and complex topology (fat tree). The measurement results showed that IDDFS, DFS, and BFS had ability to find paths and to implement multipath routing scheme. The IDDFS performance on simple topology was under the performance of other two algorithms. The measurement results of path execution time: 0.0011355 ms (DFS), 0.001461 ms (BFS), 0.0018207 ms (IDDFS); response time: 147.8 ms (DFS), 145.9 ms (BFS), 146.9 ms (IDDFS); and throughput: 16.63 Gbps (DFS), 16.79 Gbps (BFS), 16.71 Gbps (IDDFS). The IDDFS performance on complex topology was better. The measurement results of path execution time: 0.1277544 ms (DFS), 0.1760637 ms (BFS), 0.0006142 ms (IDDFS); response time: 2043.7 ms (DFS), 2396.1 ms (BFS), 298.3 ms (IDDFS); and throughput: 12.964 Gbps (DFS), 12.533 Gbps (BFS), 14.78 Gbps (IDDFS).